Efficient removal of aqueous Pb(II) using partially reduced graphene oxide-FeO - Ting Guo; Chaoke Bulin; Bo Li; Zhiwei Zhao; Huitao Yu; He Sun; Xin Ge; Ruiguang Xing; Bangwen Zhang (Adsorption Science & Technology)
Partially reduced graphene oxide-Fe 3 O 4 composite was prepared through in situ co-precipitation and used as an efficient adsorbent for removing Pb(II) from water. The composites were characterized by X-ray diffraction, high-resolution transmission electron microscopy, X-ray photoelectron spectra, Fourier transformation infrared, Raman spectrometer, N 2 adsorption–desorption, vibrating sample magnetometer, and zeta potential analyses. The impacts of pH, contact time, adsorbent dosage, temperature, and foreign substances on Pb(II) adsorption performance were investigated. The adsorption mechanism, kinetics, and thermodynamics were analyzed. The results indicate that Fe 3 O 4 is homogeneously anchored inside the thin graphene sheets, with a particle size of 15–20 nm, resulting in a very low remanence and coercivity. The composite shows excellent and efficient adsorption performance toward aqueous Pb(II): adsorption equilibrium was reached in 10 min with the adsorption percent and quantity of 95.77% and 373.14 mgċg −1 , respectively, under a condition of pH = 6, adsorbent dosage 250 mgċL −1 , and Pb(II) initial concentration 97.68 mgċL −1 , with the subsequent magnetic separation taking only 10 s. The adsorption performance is dependent on adsorbent dosage. A lower dosage favors a higher adsorption quantity, implying a strong adsorptive potential for partially reduced graphene oxide-Fe 3 O 4 . The adsorption quantity reached 777.28 mgċg −1 , given the dosage 100 mgċL −1 . The adsorption is monolayer chemisorption, the whole process of which is controlled by chemisorption and liquid film diffusion. In terms of thermodynamics, the adsorption is an exothermic and spontaneous process.